THE CONSUMER RESEARCH INDICATORS OF BREAD QUALITY WITH HERBAL SUPPLEMENTS - Yana Yurievna Starovoytova; Marina Nikolaevna Shkolnikova; Olga Viktorovna Chugunova (Современная наука и инновации)
In article approach to expansion of the range of national bakeries of products on an example focaccia is offered. Need of development of a compounding and technology focaccia from wheat flour with addition of oatmeal and vegetable powders is proved. Influence of oatmeal and vegetable powder on consumer qualities of the developed product, depending on quantity of the brought component is studied.